Experimental verification of the mathematically modelled equal-size tri-operation multilayer L and S-band antenna - Subahir, Suhaila; Esa, Mazlina (IEEE, 2004)
This paper focuses on the design of a rectangular microstrip antenna which can operate at three frequencies over the L and S-band region. The chosen frequencies are the Global Positioning System (GPS) satellite frequencies in the L-band and 2.45 GHz of the Wireless Local Area Network (WLAN) system. The main objective of this work is to experimentally verify the mathematically modelled multilayer rectangular patch antenna having three equal-size radiating elements, each operates at a different frequency within the specified bands. The feed line is located at the non-radiating edge. The MalhCAD software has been used for computing and correlating the relevant design formulations. A simple expression consisting of two variable parameters, the relative permittivity and its thickness, have been successfully developed. The three layers of the antenna have identical radiating sizes of 48 mm by 37 mm. The measured antenna exhibit well-matched frequency of operations that correspond to the simulated antennas and theory.